Liquidity: A Growing Attribute of Mortgage Loan Portfolios: Discussion - Beckhart, B. H.; Behrens, Carl F.; Emory, George N.; Hart, Shirley K.; O'Leary, James J.; Weimer, A. M. (Journal of Finance, 1950)
B. H. Beckhart, Carl F. Behrens, George N. Emory, Shirley K. Hart, James J. O'Leary, A. M. Weimer, Liquidity: A Growing Attribute of Mortgage Loan Portfolios: Discussion, The Journal of Finance, Vol. 5, No. 4 (Dec., 1950), pp. 324-336